Variation of Carbon–Nitrogen Contents and Allelopathic Disruption of Renieramycin M–Producing Sponge Xestospongia sp. in the Gulf of Thailand - Darumas, Udomsak; Salem, Gad Elsayed Mohamed; Suwanborirux, Khanit; Viyakarn, Voranop; Chavanich, Suchana (Frontiers in Marine Science, 2022)
Allelopathy is commonly found in marine sponges. However, information on allelopathic activities of sponge extracts is limited. In this study, variations of nutritional values of Xestospongia sp. were investigated. Xestospongia did not unequally distribute its nutritional values for predatory defense. Carbon–nitrogen contents and renieramycin M concentrations were not significantly different among the areas of Xestospongia sp. (edge, inner, and outer). However, carbon–nitrogen contents and renieramycin M concentrations of Xestospongia sp. coexisting with different organisms were not significantly different. In the laboratory, bleaching and necrosis of coral nubbins were not observed in every treatment, and renieramycin M did not show any allelopathic effect on its coexisting organisms (Porites lutea and Palythoa caesia). However, renieramycin M inhibited settlement of acorn barnacle (Semibalanus balanoides) but did not inhibit the settlement of pelecypods. When testing for antimicrobial effect, renieramycin M did not inhibit the growth of aerobic bacteria in any treatments. This study provides evidence that renieramycin M found in Xestospongia was uniform; however, it can possess strong inhibitory activities against some marine organisms.